Use and development of teaching technologies presented in nursing research - Pétala Tuani Candido de Oliveira Salvador; Cláudia Cristiane Filgueira Martins Rodrigues; Kálya Yasmine Nunes de Lima; Kisna Yasmin Andrade Alves; Viviane Euzébia Pereira Santos (Rev Rene)
Objective: characterizing teaching technologies used or developed in nursing dissertations and theses in Brazil. Methods: a documentary research that had data collection sourced from directories of theses and dissertations available on the website of the Brazilian Nursing Association, from Volumes Nineteen (XIX) (2001) to Twenty-one (XXI) (2013). Results: of 6346 studies, 18 (0.28%) used or developed teaching technologies, composed of the following categories: use of conceptual map; use of games; development of Virtual Learning Environment; development of educational materials; development of Distance Education courses; and artifact development. Conclusion: national research on the development and use of teaching technology in nursing are still insufficient, especially in the North and Northeast. Multiple benefits of the use of teaching technologies in nursing and learning environments were highlighted, not only for students and professionals, but also for patients.